STRATEGI PENGEMBANGAN WISATA KULINER KOTA LUBUK LINGGAU MELALUISOSIAL MEDIA INSTAGRAM @jajan_linggau - Tifanny Marchshanda; I Nyoman Sunarta, Dian Pramita Sugiarti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Culinary tourism is one of the fastest-growing tourism sectors and holds great potential in supporting the local economy, particularly through MSMEs. Lubuk Linggau City, as the second-largest city in South Sumatra Province, possesses significant culinary tourism potential. However, the utilization of social media for the development of this sector remains suboptimal. This study aims to examine the existing condition of culinary tourism in Lubuk Linggau City and to analyze development strategies implemented through the Instagram account @jajan_linggau. The research employed a descriptive-qualitative method with a case study approach, using data collection techniques such as direct observation, semi-structured interviews, and documentation. SWOT analysis was also applied to formulate development strategies culinary tourism in Lubuk Linggau City for the Instagram account as a medium of culinary promotion. The findings indicate that @jajan_linggau actively promotes local culinary MSMEs through engaging visual content, interactive captions, and the use of Instagram features such as feed, stories, and reels. The identified development strategies include collaboration with MSME actors and government, strengthening local brand image, and optimizing digital content. This study concludes that social media, particularly Instagram, plays a strategic role in developing regional culinary tourism when supported by consistent content, cross-sector collaboration, and creative and sustainable marketing approaches